2017
DOI: 10.1186/s11671-017-2116-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of the La1 − x − y Eu y Ca x VO4 (0 ≤ x, y ≤ 0.2) Compounds

Abstract: The La1 − xCaxVO4 and La1 − x − yEuyCaxVO4 (0 ≤ x, y ≤ 0.2) micro/nanosized powders were prepared by aqueous nitrate–citrate sol–gel synthesis. Phase composition of the sample depends on the x and y values. The La0.9Ca0.1VO4 is crystallized in monoclinic structure up to the x = 0.1. The La0.9Eu0.05Ca0.05VO4 sample was also attributed to the monoclinic structure. Increasing concentration of europium and calcium ions in La1 − x − yEuyCaxVO4 solid solutions leads to the change of the crystal structure, and subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 41 publications
(65 reference statements)
5
15
0
Order By: Relevance
“…The Eu 1− x Ca x VO 4 and La 1− x − y Eu y Ca x VO 4 samples with x, y = 0.05, 0.1, 0.15, and 0.20 were prepared by the aqueous nitrate–citrate sol–gel synthesis route using citric acid as a complexing agent according to procedure described in Ref. …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Eu 1− x Ca x VO 4 and La 1− x − y Eu y Ca x VO 4 samples with x, y = 0.05, 0.1, 0.15, and 0.20 were prepared by the aqueous nitrate–citrate sol–gel synthesis route using citric acid as a complexing agent according to procedure described in Ref. …”
Section: Methodsmentioning
confidence: 99%
“…Previous investigations have shown that partial replacements of the RE cations with iso‐ and heterovalent ions in the REVO 4 compounds lead to various changes of their physical and chemical characteristics . In particular, replacement of the RE cations with alkaline earth (AE) cations (Ca 2+ , Sr 2+ , Ba 2+ ) in the RE vanadate nanoparticles causes increase of luminescent intensity and arising of additional excitation band in violet spectral range of light …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations